Comparison of Intravenous Immunoglobulin (IVIG) and Intravenous anti-D for Treatment of Acute Idiopathic Thrombocytopenic Purpura - Zahra Farahmandinia; Ali Naderi; Fatemeh Sabzevari; Saeedeh Parvaresh (International Journal of Hematology-Oncology and Stem Cell Research, 2010)
"nAbstract "nIntroduction: Acute Idiopathic Thrombocytopenic purpura (ITP) is an autoimmune bleeding disorder of childhood caused by production of auto antibodies against platelets. The aim of the present study was to compare the efficacy of intravenous immunoglobulin (IVIG) and intravenous anti-D(IV anti-D) in ITP treatment. "nMethods and materials: In a clinical trial, 43 children with acute ITP referred to Afzalipour Hospital, Kerman/ Iran during 2 years were studied. Children were randomly divided into two treatment groups of IVIG (n=27) and anti-D (n=16). Two groups were compared in regard to the time takes for platelets to increase, platelets count in the 10th post-treatment day and any drug side effects. "nResults: Positive response to the treatment was observed in 70.4% (19 patients) of IVIG group and 68% (11 ones) of IV anti-D group. Mean response time was 2.9 days in anti-D and 2.8 days in IVIG groups (p=0.934). Platelets count on the 10th post-treatment day in anti-D and IVIG groups were respectively 202545/μl and 204857/μl (p=0.974). Four patients in IVIG group showed side effects, while the patients in anti-D group had no complication or acute hemoglobin decrease. "nConclusion: In spite of no significant difference between IVIG and anti-D treatment groups in regard to the therapeutic outcomes, IV anti-D is suggested as the first-line treatment in acute ITP because of its lower price, more convenient administration and no need for hospitalization.